Blast. - Naeem, Annis, ....-; Gardner, Danny, ....-; Robertson, Scott, 1966- (Culver City : Designstudio, 2012)
Following in the successful tracks of DRIVE, vehicle sketches and renderings, BLAST takes the readers on a visual exploration of spaceships. The team from DRIVE, Scott Robertson, Annis Naeem, and Danny Gardner are together again for BLAST, with each of the three artists exploring spaceships and sci-fi environments with concept sketches executed in wide range of mediums through to final full color Photoshop and 3D digital renderings. BLAST also features a guest artist section with spaceship art from Harald Belker, Ian McQue, Thom Tenery, David Hobbins, Darren Bacon and Joon Ahn. Take off with these visionaries as they launch us out of this world with their captivating spaceship creations. Following on the fast and successful treads of DRIVE, vehicle sketches and renderings, BLAST takes the readers on a visual development journey of spaceships. The formula from DRIVE is applied again to BLAST, with each of the three artists taking spaceships from preliminary concept sketch to final, fully rendered, photorealistic detail. Take off with these visionaries as they launch us out of this world with their captivating spaceship creations